Addressing Study Skills, Learning Theory and Critical Thinking Skills in Principles of Economics Courses - Howard, Eric; Sarbaum, Jeffrey (Frontiers in Education, 2022)
The Wall Street Journal recently noted that United States “employers say too many schools aren’t teaching students the skills they need—or even basic critical thinking”. This paper 1) motives the need for economics and other college educators to i) address study habits in the classroom, (ii) explain the importance of critical thinking skills, and (iii) define what critical thinking is to introductory students; and 2) provides an overview of how the authors accomplish this in their classrooms. The authors encourage readers to borrow this information to create a study skills and critical thinking module for their own students when teaching principles courses.